Applicability Study on Modified Argillaceous Slate as Subgrade Filling for High-Speed Railway - Ping Hu; Wei Guo; Limin Wei (Applied Sciences, 2022)
Modifying weathered argillaceous slate (WAS) to fill the subgrades of high-speed railways not only leads to obvious environmental benefits but also significantly saves natural resources. Previous studies have used several additives together with cement/quicklime. Using cement/quicklime as an additive would also improve the strength of weathered soft rock. Therefore, cement/quicklime can be used effectively as a sustainable solution. To illustrate the feasibility of cement/quicklime in WAS improvement, the mineral components and physical, mechanical and hydraulic characters for cement/quicklime-modified WAS were investigated via laboratory test. The dynamic behaviors were then analyzed by establishing a 3D vertical coupling dynamic model and performing dynamic triaxial tests. After mixing cement/quicklime, the following was proved: (1) The particles were coarsened, the content of kaolinite and amorphous phase increased, and the content of muscovite decreased, resulting in weakened hydrophilicity, reduced plasticity and enhanced water stability; (2) Mechanical and deformation characters were enhanced, reflecting an unconfined compression strength of quicklime/cement-modified soil greater than 0.5 MPa and elastic deformation for the subgrade of less than 0.1 mm; (3) For the quicklime-modified WAS, the dynamic strength was below the allowable value, and the sample disintegrated in water in 2 min, indicating it to be unsuitable for subgrade filling in HSR; (4) For cement-modified WAS, the water stability and dynamic strength were improved greatly, as well as the static strength. The sum of results highlights that 5% cement-modified WAS is recommended for filling subgrades of HSR for comprehensive factors.